Decoding the consecutive lysosomal degradation of 3-O-sulfate containing heparan sulfate by Arylsulfatase G (ARSG). Issue 17 (17th September 2021) - Kowalewski, Björn; Lange, Heike; Galle, Sabrina; Dierks, Thomas; Lübke, Torben; Damme, Markus
Abstract : The lysosomal degradation of heparan sulfate is mediated by the concerted action of nine different enzymes. Within this degradation pathway, Arylsulfatase G (ARSG) is critical for removing 3- O -sulfate from glucosamine, and mutations in ARSG are causative for Usher syndrome type IV. We developed a specific ARSG enzyme assay using sulfated monosaccharide substrates, which reflect derivatives of its natural substrates. These sulfated compounds were incubated with ARSG, and resulting products were analyzed by reversed-phase HPLC after chemical addition of the fluorescent dyes 2-aminoacridone or 2-aminobenzoic acid, respectively. We applied the assay to further characterize ARSG regarding its hydrolytic specificity against 3- O -sulfated monosaccharides containing additional sulfate-groups and N -acetylation. The application of recombinant ARSG and cells overexpressing ARSG as well as isolated lysosomes from wild-type and Arsg knockout mice validated the utility of our assay. We further exploited the assay to determine the sequential action of the different sulfatases involved in the lysosomal catabolism of 3- O -sulfated glucosamine residues of heparan sulfate. Our results confirm and extend the characterization of the substrate specificity of ARSG and help to determine the sequential order of the lysosomal catabolic breakdown of (3- O -)sulfated heparan sulfate.